2024
DOI: 10.1099/mgen.0.001180
|View full text |Cite
|
Sign up to set email alerts
|

Exploring the effects of antimicrobial treatment on the gut and oral microbiomes and resistomes from elderly long-term care facility residents via shotgun DNA sequencing

Norikazu Kitamura,
Toshiki Kajihara,
Camila Gazolla Volpiano
et al.

Abstract: Monitoring antibiotic-resistant bacteria (ARB) and understanding the effects of antimicrobial drugs on the human microbiome and resistome are crucial for public health. However, no study has investigated the association between antimicrobial treatment and the microbiome–resistome relationship in long-term care facilities, where residents act as reservoirs of ARB but are not included in the national surveillance for ARB. We conducted shotgun metagenome sequencing of oral and stool samples from long-term care fa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 36 publications
0
1
0
Order By: Relevance
“…The fact that 19.6% of the patients were prescribed ATBs and the negative impact of this intervention raises concerns regarding the possible impact of these drugs on the effectiveness of immunotherapy ( 28 , 29 ). It has been demonstrated that the gut microbiota, which is essential for regulating immune responses, is impacted by ATBs ( 30 ). Immunotherapy may be less effective if the composition of the microbiota is disturbed because this can hinder the immune system’s capacity to mount an effective anti-tumor response.…”
Section: Discussionmentioning
confidence: 99%
“…The fact that 19.6% of the patients were prescribed ATBs and the negative impact of this intervention raises concerns regarding the possible impact of these drugs on the effectiveness of immunotherapy ( 28 , 29 ). It has been demonstrated that the gut microbiota, which is essential for regulating immune responses, is impacted by ATBs ( 30 ). Immunotherapy may be less effective if the composition of the microbiota is disturbed because this can hinder the immune system’s capacity to mount an effective anti-tumor response.…”
Section: Discussionmentioning
confidence: 99%